KETERISIAN DAN KEAKURATAN PENULISAN KODE ICD-10 (INTERNATIONAL STATISTICAL CLASSIFICATION OF DISEASES AND RELATED HELATH PROBLEM TENTH REVISION) TERHADAP DIAGNOSIS UTAMA DI POLI BEDAH RUMAH SAKIT BAPTIS BATU - Faiqatul Hikmah; Rosalina Adi Wijayantin; Yonica Putra Rahmadtullah (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2013)
ABSTRACKThe hospital is a center of important information about health. As an information center, the hospital is expected to provide precise and accurate information. The accuracy of diagnosis coding akam disease patients are very influential in many respects, therefore, necessary writing diagnosais complete and correct disease, so as to facilitate the process codefication diagnosis based on ICD-10 disease. Researchers want to know more about the completeness and accuracy of disease diagnosis codefication by ICD-10 in Poly Stone Baptist Saki surgical house. The study was conducted in Inpatient Surgical Care and Medical Record Part Stone Baptist Hospital. This type of research is conducted by researchers dekskriptif is by analyzing the data and presenting the facts in a systematic way so that it can be easier to understand.Method used is the method of observation with Cross-Sectional approach. Observations made on the document Inpatient medical records of surgical patients Baptist Hospital Rock in January-March of 2013. From the results of a study of 71 data, the occupancy number of diagnoses and ICD-10 code medical records document the period January-March 2013 Inpatient Surgical Care RSBB complete the calculation in January 16 document medical records, February 29, and March 26, full-filled with a percentage of 100%, while the diagnosis is incomplete or not filled with as much as 0 percent 0% sample. Number of ICD-10 codes inaccuracies highest in January is by percentage of 19%, then in the second position in February with the percentage of 17% and 12% in March. There were five major diseases diagosis first quarter of 2013 in the Inpatient Surgical Poly Ca mammary RSBB is 15%, 13% inguinal hernia, acute appendicitis 11%, Multiple soft tissue lipomas 8%, 3% Benign mammary dysplasia.From the comparison of the percentages can be seen that charging the diagnosis of diseases in Poly Stone Baptist Hospital Surgical already filled out completely, but there are still some code that does not accurately diagnose illness. Factors affecting disease diagnosis inaccuracies codefication not entirely influenced by knowledge of medical officers and officers in the medical record coding, but also accuracy in recording. Therefore there needs to be an agreement of physicians, nurses poly, and personnel records medi sdalam writing code diagnosis and disease diagnosis charging properly, resulting in a diagnosis code is appropriate and accurate.Keyword: OCCUPANCY, ACCURACY, ICD-10, DIAGNOSIS OF MAJOR SURGERY